Pregnenolone sulfate regulates prolactin production in the rat pituitary. Issue 3 (September 2016) - Kang, Eun-Jin; Hong, So-Hye; Lee, Jae-Eon; Kim, Seung Chul; Yang, Hoe-Saeng; Yi, Pyong in; Lee, Sang-Myeong; An, Beum-Soo
Abstract : Pregnenolone sulfate (PS) is a neuroactive steroid hormone produced in the brain. In this study, the effects of PS on synthesis and secretion of rat pituitary prolactin (PRL) were examined. To accomplish this, GH3 rat pituitary adenoma cells were treated with PS, which showed significantly increased mRNA and protein levels of PRL compared with the control. The mechanism of action responsible for the effects of PS on PRL synthesis and secretion was investigated by pretreating cells with inhibitors of traditional PRL- or the PS-related signaling pathway. PS-stimulated PRL transcription was significantly reduced by inhibitors of PKA, PKC and MAPK, but unchanged by GABAAR and NMDAR inhibitors. Western blotting analysis revealed that the total ERK1/2 level was upregulated in a time-dependent manner following PS treatment. An approximate 10% increase in GH3 cell proliferation was also observed in response to PS relative to the control. In the animal study, levels of PRL in the pituitary and in serum were elevated by PS. PS-stimulated PRL synthesis was also found to be associated with decreased expression of PRL target genes such as GNRH1, FSHB and LHB. These findings show that PS upregulates PRL synthesis and secretion in vivo and in vitro via MAPK signaling, suggesting that it has the potential for use as a therapeutic hormone to treat PRL-related disorders such as hypoprolactinemia and low milk supply.